2019
DOI: 10.1097/bpo.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Knee Recurvatum in Children With Spastic Diplegic Cerebral Palsy

Abstract: Level III-case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The results showed that knee hyperextension was reduced in the early recurvatum group but not in the late recurvatum group after calf lengthening, which indicates early knee recurvatum is associated with calf contractures and late knee recurvatum is not associated with calf contractures and is possibly more associated with a late spastic response. Bauer et al 10 previously found that children who had knee hyperextension in early stance were more likely to have a contracture of the gastroc-soleus compared with children who had hyperextension in late stance. Therefore the majority of children with late knee recurvatum did not have calf contractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that knee hyperextension was reduced in the early recurvatum group but not in the late recurvatum group after calf lengthening, which indicates early knee recurvatum is associated with calf contractures and late knee recurvatum is not associated with calf contractures and is possibly more associated with a late spastic response. Bauer et al 10 previously found that children who had knee hyperextension in early stance were more likely to have a contracture of the gastroc-soleus compared with children who had hyperextension in late stance. Therefore the majority of children with late knee recurvatum did not have calf contractures.…”
Section: Discussionmentioning
confidence: 99%
“… 3 - 7 However, there is a subset of children that walk with knee recurvatum 8 , 9 with less known about the natural history and treatment of this pattern. Bauer et al 10 examined a cohort of children that had passive knee hyperextension on clinical exam and determined that the presence of contracture or spasticity of the gastroc-soleus complex and the consequent plantar-flexion knee extension couple led to knee hyperextension in stance phase. Bauer et al 10 also found that children who had knee hyperextension in early stance were more likely to have a contracture of the gastroc-soleus than children who had hyperextension in late stance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurvatum is an unusual deformity of the knee in children and amongst its causes are conditions such as arthrogryposis (4) , cerebral palsy (5)(6)(7) , poliomyelitis, sequelae of the tibial tuberosity fracture (8,9) , and some syndromes with generalized joint hypermobility (1,10) . When there is a structured equinus deformity of the ankle and foot, the knee with joint hypermo-bility can deform into recurvatum due to the vector resulting from the relative posteriorization of the proximal tibia and anteriorization of the load axis to the knee.…”
Section: Introductionmentioning
confidence: 99%
“…Both congenital and acquired etiologies can give rise to genu recurvatum, with variable clinical presentation. [1][2][3][4][5][6] Nonoperative management may be appropriate for select patients, but a greater magnitude of anterior tibial slope is often effectively treated with anterior opening wedge high tibial osteotomy (OW-HTO), with or without external fixation 7 . Occasionally, genu recurvatum coincides with coronal malalignment (e.g., genu valgum), which may complicate surgical planning.…”
mentioning
confidence: 99%